Look good! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
An illustration (photo, drawing, cartoon, etc.) always gets noticed by the reader first, before the words. A picture can inspire or trigger off a dream, and is at least as powerful as a text. A photograph is not an ornament; it can bring home a...